Safeguarding nutritional opportunities of first 1000 days of life during a pandemic: infant and young children feeding practices in the context of COVID-19 in India - Varghese, Anila; Agarwal, Monika (International Journal Of Community Medicine And Public Health, 2020)
Children have milder clinical course and better prognosis from SARS-Co-V-2 infection. But the after-effects of this pandemic can have severe repercussions on nutrition of children, especially those who are already malnourished. Poor nutrition in the first 1,000 days of a child’s life can lead to stunted growth, which is associated with impaired cognitive ability and reduced school and work performance. Misconceptions about breastfeeding, food insecurity hampering the procurement of nutritious food, competing household needs, psychological trauma that affects child care practices and disruption or reduced utilization of routine nutrition services can negatively impact infant feeding during the pandemic. If nutrition related factors contributed to about 45% of global under-5 mortality before the onset of COVID-19, the figures can increase if appropriate infant and young child feeding practices are not followed. Years of dedicated work has resulted in the infant feeding indicators we cite today. Efforts should be made to prevent backsliding, resulting in increased child malnutrition and mortality. Appropriate measures at the right time to protect, promote and support optimal IYCF practices and thereby safeguard the nutritional benefits of the first 1000 days of life during this pandemic, will pay rich dividends in terms of a healthier next generation.